Neglected diseases of neglected populations: Thinking to reshape the determinants of health in Latin America and the Caribbean - Ehrenberg, John P (BioMed Central, 2005)
BACKGROUND: People living in poverty throughout the developing world are heavily burdened with neglected communicable diseases and often marginalized by the health sector. These diseases are currently referred to as Neglected Diseases of Neglected Populations. The neglected diseases create social and financial burdens to the individual, the family, the community, and the nation. DISCUSSION: Numerous studies of successful individual interventions to manage communicable disease determinants in various types of communities have been published, but few have applied multiple interventions in an integrated, coordinated manner. We have identified a series of successful interventions and developed three hypothetical scenarios where such interventions could be applied in an integrated, multi-disease, inter-programmatic, and/or inter-sectoral approach for prevention and control of neglected diseases in three different populations: a slum, an indigenous community, and a city with a mix of populations. SUMMARY: The objective of this paper is to identify new opportunities to address neglected diseases, improve community health and promote sustainable development in neglected populations by highlighting examples of key risk and protective factors for neglected diseases which can be managed and implemented through multi-disease-based, integrated, inter-programmatic, and/or inter-sectoral approaches. Based on a literature review, analysis and development of scenarios we visualize how multiple interventions could manage multiple disease problems and propose these as possible strategies to be tested. We seek to stimulate intra- and inter-sectoral dialogue which will help in the construction of new strategies for neglected diseases (particularly for the parasitic diseases) which could benefit the poor and marginalized based on the principle of sustainability and understanding of key determinants of health, and lead to the establishment of pilot projects and activities which can contribute to the achievement of the Millennium Development Goals.